2020
DOI: 10.1111/iej.13356
|View full text |Cite
|
Sign up to set email alerts
|

The impact of two root canal treatment protocols on the oral health‐related quality of life: a randomized controlled pragmatic clinical trial

Abstract: Aim To assess the impact of two root canal treatment protocols on the oral health‐related quality of life (OHRQoL) of patients in need of root canal treatment on their anterior teeth. Methodology The sample consisted of 120 participants (mean age: 34 years) enrolled in a pragmatic randomized clinical trial evaluating two root canal treatment protocols. Anterior teeth with nonvital pulps were allocated for root canal preparation with either hand files and filled with lateral compaction of gutta‐percha (manual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“… 61 In terms of surgical endodontics, the use of microsurgical protocols, 53 peizosurgery instruments, 46 papilla-based flap designs, 48 low-level laser therapy, 56 and autologous platelet concentrates have also been evaluated in the context of PROMs. Except for the study by Diniz-de-Figueiredo et al, 65 the period of evaluation was relatively short, spanning 2 weeks at most. Again, short evaluation times may be insufficient to thoroughly assess OHRQoL beyond patients’ initial recovery.…”
Section: Reviewmentioning
confidence: 97%
See 3 more Smart Citations
“… 61 In terms of surgical endodontics, the use of microsurgical protocols, 53 peizosurgery instruments, 46 papilla-based flap designs, 48 low-level laser therapy, 56 and autologous platelet concentrates have also been evaluated in the context of PROMs. Except for the study by Diniz-de-Figueiredo et al, 65 the period of evaluation was relatively short, spanning 2 weeks at most. Again, short evaluation times may be insufficient to thoroughly assess OHRQoL beyond patients’ initial recovery.…”
Section: Reviewmentioning
confidence: 97%
“…A decrease in pain was associated with an increased in OHRQoL (POQoL scores). Diniz-de-Figueiredo et al 2020 65 Randomised controlled trial; Brazil 88 patients at 6 months (46 manual group, 42 reciprocating group); 87 patients at 12 months (42 manual group, 45 reciprocating group) Reciprocating instrumentation and single cone obturation vs hand file instrumentation and lateral compaction obturation Prior to treatment and 6 and 12 months after treatment OHIP-14 Brazilian version Yes OHRQoL improved (OHIP-14 scores decreased) significantly after root canal treatment with moderate to large effect sizes. At 6 months, the manual protocol was associated with poorer OHIP-14 scores.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A lower incidence of postoperative pain has also been reported when using rotary than manual shaping (Arias et al, 2015 ), and a poorer oral health–related quality of life 6 months after the manual shaping of anterior teeth compared with a reciprocating preparation, although with no differences after 12 months (Diniz‐de‐Figueiredo et al, 2020 ). Root canal preparation time was also lower for rotary shaping when compared with manual preparation in a clinical study that also demonstrated a comparable flare‐up incidence with both (Makanjuola et al, 2018 ).…”
Section: Reviewmentioning
confidence: 98%